(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This study approaches avital problem regarding social sciences in general, and sociology in particular, signified in the origin of the scientific social research methodology at IbnKhaldoun. It focuses on the discussion of the methodological basis and rules, and the scientific thoughts presented by IbnKhaldoun and demanded the researchers to comply with in achieving their scientific researches. In addition, it depicts the view points of some other researchers who came after Ibn Khaldoun about some of the issues he approached . The Researcher , in his approach, uses the descriptive analytical method to acquaint himself with the coherence and contrast between them, starting from the researcher’s belief in the fact that the change in the handled phenomena’s surrounding circumstances from aphase to phase and from a society to another, demands researchers not only to make benefit from ex- researchers, but promote it and furnish it with what comes in coherence with the requirements of status quo. Subjects approached by the researcher : Ahint on Research Methodology at Ibn Khaldoun, and his comprehension of social phenomena, and his view point about the relation between man and nature, his objectivity, his opinion in social development, and his educational thoughts. In conclusion, the research pointed out some sides where in the originality of research methodology at Ibn Khaldoun exists .